REPETRO - Regime Aduaneiro Especial de Importação e Exportação de Bens Destinados à Pesquisa e Lavra de Petróleo e Gás: análise dos entraves e propostas de soluções - Silva, Tom Pierre Fernandes da (2007)
REPETRO, the special tax regime for importing and exporting goods for the exploration and drilling of oil and gas, aims at bringing foreign assets to Brazil enjoying a suspension or even an exemption of taxes, so that Brazilian industry may profit from about 8 billion American dollars in investments. The creation of normative devices as well as the management of the REPETRO model are under the exclusive responsibility of the Brazilian Internal Revenue Services. REPETRO was created in 1999 and is composed of the following customs treatments: importation of goods with suspension of taxes by use of the drawback special regime, suspension mode for national exporting industry; exportation with fictitious exit for the national industry; temporary admission of goods or assets used in oil exploration and production, attending to the needs of both the national and foreign market. Considering the inability of the Brazilian government in restructuring its foreign trade model so that a strong investment in technology could provide for the sector¿s needs, we must ask how we can change REPETRO to help the various companies in the oil business? The issue is very important for one of our main economic activities, though not enough studied. The energy sector has a strategic importance for the development and the economic independence of any country. The winds of globalization lead Brazil to open its economy in the last decade and the national policy for exploration and drilling (E&D) was altered. The government created a new agency dedicated to market control and energy policies, the National Agency for Oil and Biofuels (ANP). With the opening of the market, Petróleo Brasileiro S.A. - Petrobras, the Brazilian giant, lost the monopoly of the oil business. The P-50 Platform, with a capacity for 180,000 barrels per day, was imported based on REPETRO. When it began operating on April 21st, 2006, Brazil achieved self-sufficiency in oil production. The present work intends to estimate the main variables affecting the importation and exportation of goods and assets for E&D, showing how REPETRO works. We also intend to look at the results yielded by the REPETRO model for the development of the production of oil and gas in Brazil, as well as show proposals for its modernization. It has been established that even though since its implementation the REPETRO model has brought fiscal advantages through the reduction of tax costs relating to foreign commerce operations and the incentive of investments in the E&D area with the increase in the national oil production there remain the following limitations: lack of preparation and of knowledge of the model; lack of adjustement of the model to the reality of actitity of E&D of oil and gas; taxes over the pre-operational stage or investment in oil production stage; non-allowance of full access by the national industry to the supply of goods and products relating to the industrialization of goods allowed by REPETRO; other fiscal and administrative difficulties. We conclude that the REPETRO model is important for the development of the area of E&D of oil and gas, but not completely effective. It is necessary to change it or create a new model based on a new perspective of the customs treatment of the activities of exploration and production, minimizing administrative procedures relating to the operations of exportation and importation.